a 2 cot 9 ∘ + b 2 cot 2 7 ∘ + c 2 cot 6 3 ∘ + d 2 cot 8 1 ∘
Let a , b , c and d be real numbers satisfying a + b + c + d = 5 . If the minimum value of the expression above is equal to y x , where x and y are coprime positive integers, find x + y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
That is a great way of answering Mr. Kahayon
LAKAZ NI OSBERT!!!
Log in to reply
Hindiiii poooooo
Log in to reply
Out of curiosity,what is the meaning of 'hindi' here.Do you mean Hindi(lang.)?
Log in to reply
@Rohit Udaiwal – No... Hindi means no in filipino language..
How did you go from 2(csc 18 + csc 54) to 4sqrt5?
Log in to reply
c s c 1 8 = s i n 1 8 1 = 5 − 1 4 = 5 + 1 (A less well-known special angle)
Similarly, c s c 5 4 = s i n 5 4 1 = 5 + 1 4 = 5 − 1 (Another less well-known special angle)
So, 2 ( c s c 1 8 + c s c 5 4 = 2 ( 5 − 1 + 5 + 1 ) = 4 5
Let us take a general case where x + y = k and p = a x 2 + b y 2 which is to be minimised.
⇒ p = ( a + b ) x 2 − ( 2 k b ) x + b k 2 or p = ( a + b ) y 2 − ( 2 k b ) y + b k 2
So, x m i n = a + b b k and y m i n = a + b a k
∴ p m i n = a + b a b k 2 - - - ( 1 )
So, p = a 2 cot 9 ∘ + b 2 cot 2 7 ∘ + c 2 cot 6 3 ∘ + d 2 cot 8 1 ∘ can be minimised as follows:
p 1 = a 2 cot 9 ∘ + d 2 cot 8 1 ∘
p 2 = b 2 cot 2 7 ∘ + c 2 cot 6 3 ∘
p m i n = p 1 m i n + p 2 m i n where p 1 = 2 s i n 1 8 ∘ k 1 2 ; p 2 = 2 c o s 3 6 ∘ k 2 2 , a + d = k 1 ; b + c = k 2 and k 1 + k 2 = 5
∴ p m i n = 4 1 2 5 (using ( 1 ) )
Nice problem. From where do you got this
Log in to reply
It was given to me by my maths teacher.
PS- Not school teacher :P
Problem Loading...
Note Loading...
Set Loading...
By Cauchy-Schwarz inequality,
( a 2 cot 9 ∘ + b 2 cot 2 7 ∘ + c 2 cot 6 3 ∘ + d 2 cot 8 1 ∘ ) ( cot 9 ∘ 1 + cot 2 7 ∘ 1 + cot 6 3 ∘ 1 + cot 8 1 ∘ 1 ) ≥ ( a + b + c + d ) 2 = 2 5 (Since a + b + c + d = 5
Now, let ( a 2 cot 9 ∘ + b 2 cot 2 7 ∘ + c 2 cot 6 3 ∘ + d 2 cot 8 1 ∘ ) = N Then, dividing both sides by cot 9 ∘ 1 + cot 2 7 ∘ 1 + cot 6 3 ∘ 1 + cot 8 1 ∘ 1 ,
N ≥ cot 9 ∘ 1 + cot 2 7 ∘ 1 + cot 6 3 ∘ 1 + cot 8 1 ∘ 1 2 5 = tan 9 ∘ + tan 8 1 ∘ + tan 2 7 ∘ + tan 6 3 ∘ 2 5
Now, by the identity tan x ∘ + tan ( 9 0 − x ) ∘ = 2 csc ( 2 x ) , we see that tan 9 ∘ + tan 8 1 ∘ + tan 2 7 ∘ + tan 6 3 ∘ = 2 ( csc 1 8 ∘ + csc 5 4 ∘ ) = 4 5
Therefore, N ≥ tan 9 ∘ + tan 8 1 ∘ + tan 2 7 ∘ + tan 6 3 ∘ 2 5 = 4 5 2 5 = 4 1 2 5
Our answer is 1 2 5 + 4 = 1 2 9